Medicinal plants used for treating infertility and related disorders of women in India: a systematic review - Sharma, Pramod Parasharam; Sharma, Sakshi Pramod (International Journal of Research in Medical Sciences, 2023)
Assessment of plant medicine for treating infertility and related disorders is making headway universally recent couple of decades to bring out new effective and safe substances as an alternative medicine. Present paper reviews the published literature on plant medicine used for female infertility and related disorders. The 53 research papers or reports shortlisted are based studies under taken in India. Total 459 uses of 202 medicinal plants classified under 84 families. Total 62 trees, 55 shrubs, 79 herbs and 3 climbers are reported. Most used plant parts for making medicine are roots in 111 formulations and leaf in 101 formulations. Medicinal plants used for infertility are 84, while for related disorder like leucorrhoea 79 plants, menorrhagia 53, dysmenorrhea 29, amenorrhea 23 and 22 plants used to regulate menstruation. Additional investigations could be helpful to verify the claims reported using a specific formulations or recipes and which will subsequently result in providing possible the alternative medicine for the treatment of female infertility.